Effects of Different Water Treatments on Plant Growth and Yield of Lycium Barbarum in Northern Xinjiang - Jiazila; Sulitan; Bai Yungang (Shuitu baochi tongbao)
[Objective] The irrigation system suitable for the cultivation of Lycium barbarum in Northern Xinjiang Uygur Autonomous Region was studied to provide a scientific basis for the future irrigation of L. barbarum in this area. [Methods] The plant height, stem thickness, crown width, water consumption, and yield of L. barbarum were monitored, and the effects of different irrigation amounts and irrigation frequencies on the growth and yield of drip-irrigated L. barbarum were analyzed. [Results] ① Plant height of drip-irrigated L. barbarum increased with increasing irrigation amount annually. ② Annual net growth of drip-irrigated L. barbarum stem thickness increased with increasing irrigation amount. When the irrigation amount increased to a certain value, the increase in stem thickness decreased. ③ The water consumption intensity of drip-irrigated L. barbarum in each growth period followed the order of fruiting stage>bloom stage>spring shoot growth stage>autumn shoot growth stage> leaf opening stage. The relationship between water consumption and yield and between water consumption and water use efficiency (WUE) of drip-irrigated L. barbarum followed a quadratic parabolic relationship. ④ When water consumption increased from 583 mm to 676 mm, yield of drip-irrigated L. barbarum increased from 12 703.5 kg/hm2 to 14 200.5 kg/hm2. At the same time, WUE of drip-irrigated L. barbarum dereased from 1.45 kg/mm to 1.46 kg/mm, it did not decrease significantly. [Conclusion] In order to save water and produce high yields, we recommend drip-irrigated L. barbarum grown in the study area be provided with 5 700 m3/hm2 of irrigation water over the entire growing season, applied as 10 irrigations of 570 mm during each application. The 10 irrigations should be applied as one irrigation during the leaf opening stage, two irrigations during the spring shoot growth stage, one irrigation during the bloom stage, four irrigations during the fruiting stage, and two irrigations during the autumn shoot growth stage.